Correlates of cognitive impairment in patients with chronic kidney failure on haemodialysis: Systematic review and meta‐analysis. (10th January 2019) - Oh, HyunSoo; Mo, JinA; Seo, WhaSook
Abstract: Aim: To review and identify correlates of cognitive impairment in patients with chronic kidney failure (CKF) on haemodialysis. Background: The literature is consistent with regard to the high prevalence of cognitive impairment among patients with CKF on haemodialysis and its dependence on multidimensional risk factors. Design: Systematic review and meta‐analysis based on Cochrane Handbook and PRISMA. Data sources: Electronic searches of the MEDLINE, EMBASE, Cochrane Library databases and major Korean databases were used. Only original research that assessed correlates of cognitive impairment in patients with CKF on haemodialysis and published between 2004–2016 in English or Korean were included. Review methods: Studies were selected according to the PICOS: Population (chronic kidney failure patients with cognitive impairment on haemodialysis); Intervention (not applicable); Comparison (healthy controls or patients with chronic kidney failure on haemodialysis without cognitive impairment); Outcome (cognitive impairment); and Study design (primarily nonexperimental correlational studies and studies with experimental, quasi‐experimental, or pre–post cohort designs). Q ‐test and I 2 index were used to examine study homogeneity. Results: A total of 39 studies were finally included. Age, gender, stroke history, difficulties in activities of daily life, haemoglobin levels, pain, sleep difficulties, and depression were found to be significant correlates of cognitive impairment. Conclusions: Nurses should be aware that the risk of cognitive impairment in patients with CKF on haemodialysis can be significantly higher for elders, women and in patients with a stroke, greater difficulties in activities of daily living, lower haemoglobin concentrations, higher pain levels, sleep difficulties, or depression. Abstract : 目的: 回顾和确定慢性肾功能衰竭血液透析患者认知功能损害的相关因素。 背景: 关于慢性肾功能衰竭血液透析患者血液透析后认知功能损害的高发生率及其对多维危险因素的依赖性, 文献报道是一致的。 设计: 基于考科兰手册和PRISMA的系统回顾和综合分析。 资料来源: 使用联机医学文献分析和检索系统、荷兰医学文摘数据库、考科兰图书馆数据库和主要韩国数据库的电子检索。只有在2004年至2016年期间以英文或韩文发表的原创研究评估了接受血液透析的慢性肾功能衰竭血液透析患者认知损害的相关关系。 审核方法: 根据PICOS选择研究对象:人群(慢性肾功能衰竭伴认知功能障碍的血液透析患者);干预(不适用);比较(健康对照组或慢性肾功能衰竭患者行血液透析无认知功能障碍);结果(认知障碍);研究设计(主要是非实验性相关研究, 以及与实验、准实验或队列前设计相关的研究)。Q‐测试和 I 2指数用于检验研究的同质性。 结果: 最终纳入39项研究。研究结果年龄、性别、中风史、日常生活活动困难、血红蛋白水平、疼痛、睡眠困难和抑郁与认知障碍有显著相关。 结论: 护士应该注意到, 接受血液透析的慢性肾功能衰竭血液透析患者的认知障碍风险在老年人、妇女和中风患者中可能明显更高, 日常生活活动难度更大, 血红蛋白浓度更低, 疼痛程度更高, 睡眠困难或抑郁。